2020
DOI: 10.3390/jcm9072063
|View full text |Cite
|
Sign up to set email alerts
|

Diet: A Specific Part of the Western Lifestyle Pack in the Asthma Epidemic

Abstract: The Western lifestyle is a complex concept that includes the diet as the main axis of different factors which contribute to a detrimental effect on health, lower life expectancy and low quality-of-life. This type of diet is characterized by being high in calories, mainly provided by saturated fats, and rich in sugars that can lead to changes in immune cells and their responsiveness, by different mechanisms that have yet to be totally clarified. Inflammatory processes are perpetuated through different p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 103 publications
(123 reference statements)
2
11
0
Order By: Relevance
“…For instance, alterations in the gut microbiota caused by a Western high-fat diet have recently been recognized as a major contributing factor to the colorectal cancer epidemic ( 32 ) . High -sucrose- high - fat dietary patterns were supposed to participate in the asthma pathogenesis through intestinal bacteria ( 33 , 34 ). Currently, there is not related research on whether dietary factors are involved in the pathology of MG.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, alterations in the gut microbiota caused by a Western high-fat diet have recently been recognized as a major contributing factor to the colorectal cancer epidemic ( 32 ) . High -sucrose- high - fat dietary patterns were supposed to participate in the asthma pathogenesis through intestinal bacteria ( 33 , 34 ). Currently, there is not related research on whether dietary factors are involved in the pathology of MG.…”
Section: Introductionmentioning
confidence: 99%
“…Several meta-analyses have suggested that fruit and vegetable consumption may reduce the risk of asthma due to their antioxidant effects 27 28. There are also some studies suggesting that the Mediterranean diet that is rich in vegetables and fruits, correlated negatively with the risk of asthma compared with the Western diet 6 7. As vegetables and fruits are the main sources of carotenoids, these studies indirectly suggested that carotenoid intakes reduce asthma risk.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence showed that oxidative stress is involved in the pathophysiological mechanism of asthma and implicated in the inflammation and severity of asthma 3–5. Dietary epidemiological evidence suggests that Western diets, characterised by high intake of saturated fats and simple sugars, are related to an increased incidence of asthma 6 7. While Mediterranean diets, characterised by an intake of plant-based foods (mainly vegetables and fruits), may reduce the risk of asthma through its antioxidant and anti-inflammatory effects 8…”
Section: Introductionmentioning
confidence: 99%
“…In homeostatic conditions, the healthy gut microbiota can efficiently prevent pathogen infection, reducing the chance of developing inflammation 17 . On the contrary, early life gut dysbacteriosis may lead to altered immune response and chronic inflammatory respiratory disorders, especially childhood asthma 18 . Therefore, people are gradually paying attention to the role of gut microbiota and gut‐lung axis in asthma, as well as the mechanism of gut microbiota affecting homeostasis and susceptibility to asthma 19 .…”
Section: Introductionmentioning
confidence: 99%